Managing the Long-term Preservation of Electronic Archives or Preserving the Medium and the Message - Grimard, Jacques (Archivaria, 2005)
The author invites readers to reflect on the use of electronic records. He defines the term as encompassing all those records produced and accessible only by means of electronic equipment. He shows that electronic information must be maintained through a global approach that preserves both the medium and the message. He underlines the opaque nature of electronic information, which has no natural structure even though it is regulated by a range of codes and conventions; the multiplicity of formats in which it is found; and the fluidity and malleability that characterize it. He proposes three solutions to the problem of preserving the contents of electronic records: changing the medium, standardizing formats, and conversion of the information. In the third part of his paper the author examines the fragility of electronic media and the lifespan of supporting technology. As solutions to the problem of preserving the media, the author underlines the importance of storage conditions, information conversion, research, and standardization. In conclusion, he reminds readers of the importance of preserving recorded memory. To succeed, not only must the message and the medium be preserved, but early, appropriate, and timely intervention is needed. RÉSUMÉ L’auteur invite les lecteurs à une réflexion sur l’utilisation des archives électroniques. Par ce terme il entend toutes les archives produites et accessibles seulement par le truchement d’instruments électroniques. Il montre que le maintien de l’information doit se faire dans une démarche globalisante et qu’il faut préserver à la fois le médium et le message. Il insiste sur l’opacité de l’information électronique qui n’offre aucune structure naturelle quoique régie par un éventail de codes et de conventions, sur la multiplicité des formats et sur la mobilité et la maléabilité de cette information électronique. Il propose trois solutions pour la préservation du contenu : le transfert de support, la normalisation des formats et la conversion de l’information. En troisième partie, l’auteur se penche sur la fragilité des supports et sur la durée de vie des technologies de soutien. En guise de solutions à ce problème des contenants, l’auteur insiste sur les conditions d’entreposage, la conversion de l’information, la recherche et la normalisation. En conclusion, l’auteur nous rappelle l’importance de la conservation de la mémoire documentaire. Pour ce faire, il faut non seulement préserver le message et le médium mais il faut également intervenir tôt en prenant les décisions au bon moment.